2017
DOI: 10.1007/s12288-016-0766-8
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Estimation of Haemoglobin Content in Dried Blood Spot Samples

Abstract: The ability to use indirect cyanmethemoglobin method using 20 µl of dried blood spots (DBSs) on filter paper for the analysis of haemoglobin (Hb) levels could be an important diagnostic tool for areas that have limited access to laboratory facilities. We assessed the validity of a method for Hb estimation in which a single drop of whole blood was directly taken on the filter paper. We collected 124 DBSs containing 20 µl of blood (filter paper A) and single drop of whole blood (filter paper B) from subjects liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Similar to filter paper C in our study, a study was done to validate the DBS taken directly on filter paper and concluded that the filter paper method is an effective and convenient method for conducting surveys, but only after applying a correction factor. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to filter paper C in our study, a study was done to validate the DBS taken directly on filter paper and concluded that the filter paper method is an effective and convenient method for conducting surveys, but only after applying a correction factor. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…This DBS of 5 mm in diameter was transferred in a labelled test tube containing 1.25 ml Drabkin solution (DBS of 5 mm in diameter is considered to contain 5 μl of blood). [ 8 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation